Diet, sleep and depression: Does adherence to the mediterranean diet matter? - Bakırhan, Hande; Pehlivan, Merve; Özyürek, Fatmanur; Özkaya, Volkan; Yousefirad, Neda (Galenos Publishing, 2022)
Objective: The objective of this research is to examine the relationship between Mediterranean diet pattern, depression, and sleep quality. Materials and Methods: Mediterranean diet adherence score, Beck depression inventory, and Pittsburgh sleep quality index have been applied to volunteering participants (n=250) to examine their adherence to the Mediterranean diet, sleep quality, depression status, and the correlations between these variables have been analysed. Results: Those following the Mediterranean diet pattern at a high level were found to have significantly higher sleep quality and less depression symptoms than those following this diet pattern at poor and moderate level (p<0.001). The Mediterranean diet pattern was found to be positively correlated with sleep quality and negatively correlated with BMI and depression symptoms (1 . .4).349, p<0.01, r=-0.135, p<0.05, r=-0.294, p<0.01). Low levels of depression were found to be associated with more daily consumption of vegetables, fruits, olive oil, less consumption of red meat, sugary/carbonated beverages, and sweet/pastry products, and consumption of sauce types with olive oil/tomato/garlic and olive oil being the most frequently consumed oil types (r=-0.140, r=-0.156, r=-0.169, r=-0.236, 1=-0.160, r=-0.160, r=-130, r=-0.184, p<0.05). Daily consumption of vegetables, fruits, olive oil, reduced consumption of red meat and sweet/bakery products, weekly consumption of hazelnuts/ pistachios/almonds/walnuts, and olive oil being the most frequently consumed type of oil are associated with good sleep quality (r=-0.202, r=-0.173, r=-0.244, r=-0.149, r=-0.191, r=-0.171, r=-0.225, p<0.05). Conclusion: Mediterranean diet pattern can be integrated into strategies of sleep quality and mental health improvement, as it has been associated with good sleep quality and lower depression levels.

Amaç: Bu çalışmada Akdeniz diyeti paterni, depresyon durumu ve uyku kalitesi arasındaki ilişkinin saptanması amaçlanmıştır. Gereç ve Yöntem: Rastgele örnekleme yöntemiyle seçilmiş gönüllülere (n=250) Akdeniz diyeti bağlılık ölçeği, Beck depresyon envanteri ve Pittsburgh uyku kalitesi indeksi uygulanarak Akdeniz diyeti paternini sergileme durumu, uyku kalitesi ve depresyon durumu saptanmış ve aralarındaki korelasyon değerlendirilmiştir. Bulgular: Akdeniz diyeti paternini iyi düzeyde sergileyenlerin kötü ve orta düzeyde sergileyenlere göre uyku kalitesi anlamlı şekilde daha yüksek ve depresyon belirtileri daha az bulundu (p<0,001). Akdeniz diyeti paterni uyku kalitesi ile pozitif, beden kitle indeksi ve depresyon durumu ile negatif yönde anlamlı derecede ilişkili idi (r=-0,349, p<0,01, r=-0,135, p<0,05, r=-0,294, p<0,01). Günlük sebze, meyve, zeytinyağı tüketimi, azaltılmış kırmızı et, şekerli/gazlı içecekler tüketimi ve tatlı/ pastane ürünler tüketimi, zeytinyağlı/domatesli/sarımsaklı sos tüketimi ve en çok kullanılan yağ türünün zeytinyağı olması ile düşük depresyon seviyeleri ilişkili bulundu (r=-0,140, r=-0,156, r=-0,169, r=-0,236, r=- 0,160, r=-0,160, r=-130, r=-0,184, p<0,05). Günlük sebze, meyve, zeytinyağı tüketimi, azaltılmış kırmızı et ve tatlı/pastane ürünler tüketimi, haftalık fındık/fıstık/badem/ceviz tüketimi ve en çok kullanılan yağ türünün zeytinyağı olması iyi uyku kalitesi ile ilişkili idi (r=-0,202, r=- 0,173, r=-0,244, r=-0,149, r=-0,191, r=-0,171, r=-0,225, p<0,05). Sonuç: Akdeniz diyeti paterni, iyi uyku kalitesi ve daha düşük depresyon durumu ile ilişkili bulunduğundan, uyku kalitesi ve mental sağlığı geliştirmeye yönelik stratejilere entegre edilebilir.
Diyet, uyku ve depresyon: Akdeniz diyetine uyum önemli mi?
Keywords: Mediterranean Diet; Depression; Sleep; Nutrition; Akdeniz Diyeti; Depresyon; Uyku; Beslenme